MODEL PERILAKU SYARIAH DALAM PENGAMBILAN KEPUTUSAN INVESTASI PADA INVESTOR MUSLIM DI BURSA EFEK INDONESIA - Dihin Septyato; Sudarwan .; Ignatius Joko Dewanto (UPT Penerbitan Universitas Jember)
The aim of this study was to determine the model of Islamic sharia investor behavior in their intent to invest in stock investment decisions to maximize sharia in the Jakarta Stock Exchange. Data collection method was survey. The type of data in a form of expression, experience, or the characteristics of the study subjects individually. The dimension of time is one shot study. The respondents were investors Muslim in Indonesian Capital Market by the number of 120 respondents. The results showed that Islamic investors of all ages scattered adults and there is still the largest in the productive age range 41-45 years, as for the dominant factor in the decision making on the ratings outlook for shares in fundamental knowledge than the technical aspects. Attitude and confidence in the intention to invest, the revision of the decision-making of investors through stock ratings prospects based on the merits of financial information, price information, and hamblumminannas, hablumminallah factors have a significant influence.